1996
DOI: 10.1518/001872096778827260
|View full text |Cite
|
Sign up to set email alerts
|

Aurally Aided Visual Search under Virtual and Free-Field Listening Conditions

Abstract: We examined the minimum latency required to locate and identify a visual target (visual search) in a two-alternative forced-choice paradigm in which the visual target could appear from any azimuth (0 degree to 360 degrees) and from a broad range of elevations (from 90 degrees above to 70 degrees below the horizon) relative to a person's initial line of gaze. Seven people were tested in six conditions: unaided search, three aurally aided search conditions, and two visually aided search conditions. Aurally aided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 6 publications
7
47
1
Order By: Relevance
“…1 The present study was designed to replicate and extend Van der Burg et al's (2008) findings using the auditory-visual pip-and-pop and vibrotactile-visual poke-and-pop paradigms to explore how visual search performance is modulated by cues that were not only temporally synchronous (presented in synchrony with the color change of the visual target) but also spatially informative with regard to the likely location of the target (in the left or right hemifield). The benefits of having auditory or tactile cues that are either temporally synchronous (e.g., Chan & Chan, 2006;Dalton & Spence, 2007;Van der Burg et al, 2008Vroomen & de Gelder, 2000) or spatially informative (Ho, Santangelo, & Spence, 2009;Ho, Tan, & Spence, 2006;Perrott et al, 1996;Perrott et al, 1991) have been repeatedly demonstrated trade-offs (see Spence, Kingstone, Shore, & Gazzaniga, 2001;Townsend & Ashby, 1983). IE scores were calculated by dividing each participant's mean RT for each condition by their proportion of correct responses for that condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The present study was designed to replicate and extend Van der Burg et al's (2008) findings using the auditory-visual pip-and-pop and vibrotactile-visual poke-and-pop paradigms to explore how visual search performance is modulated by cues that were not only temporally synchronous (presented in synchrony with the color change of the visual target) but also spatially informative with regard to the likely location of the target (in the left or right hemifield). The benefits of having auditory or tactile cues that are either temporally synchronous (e.g., Chan & Chan, 2006;Dalton & Spence, 2007;Van der Burg et al, 2008Vroomen & de Gelder, 2000) or spatially informative (Ho, Santangelo, & Spence, 2009;Ho, Tan, & Spence, 2006;Perrott et al, 1996;Perrott et al, 1991) have been repeatedly demonstrated trade-offs (see Spence, Kingstone, Shore, & Gazzaniga, 2001;Townsend & Ashby, 1983). IE scores were calculated by dividing each participant's mean RT for each condition by their proportion of correct responses for that condition.…”
Section: Methodsmentioning
confidence: 99%
“…Under such conditions, the presentation of spatially informative cues may offer an effective means not only of reducing the time needed to detect potential threats but also of improving the subsequent discrimination of those threats. The presentation of spatially informative nonvisual cues-specifically, auditory cues that are colocalized with visual targets-has been shown to reduce visual search latencies by several thousand milliseconds for peripherally located visual targets (i.e., for targets presented at eccentricities exceeding 90º from central fixation; see, e.g., Perrott, Cisneros, McKinley, & D'Angelo, 1996;Perrott, Saberi, Brown, & Strybel, 1990;Perrot, Sadralodabai, Saberi, & Strybel, 1991). The p presentation of spatially uninformative auditory cues has also been shown to reduce visual search latencies for vin sual targets presented in the central field by more than 200 msec (e.g., Dufour, 1999;Perrott et al, 1996;Perrott et al, 1991).…”
mentioning
confidence: 99%
“…Many researchers have investigated the utility of three-dimensional (3D) auditory displays for reducing the workload associated with an overloaded visual channel and for enhancing the detection and identification of visual targets (Flanagan, McAnally, Martin, Meehan, & Oldfield, 1998;Nelson et al, 1998;Perrott, Cisneros, McKinley, & D'Angelo, 1996). Advances in digital signal-processing technology and the development of electromagnetic position trackers have enabled the construction of small, relatively inexpensive spatial audio displays that can be used to aid in visual target acquisition in aircraft cockpits, ground combat vehicles, and training simulators.…”
Section: Introductionmentioning
confidence: 99%
“…Perrott and his colleagues have investigated the effect of the addition of an audio cue colocated with the visual target on visual search times (Perrott, et al, 1990(Perrott, et al, , 1996Perrott, Sadralodabai, Saberi, & Strybel, 1991). In one experiment (Perrott et al, 1991) Perrott et al (1996) investigated the trivial case (i.e., one target, zero distractors) of an aurally aided visual search task in which the visual field was less restricted.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of 3-D auditory displays is to create spatially arranged auditory icons for situations where it is either natural to have audible information passed or where, for instance, the visual information channel is not available or is fully occupied, e. g., [17,21,82,85]. The sound of a fuel tank drying out could carry an important message for a pilot, and the sound of a printer could be a way to transfer the graphical interfaces of modern computers into something blinds can use.…”
Section: -D Auditory Displaysmentioning
confidence: 99%